Clinical efficacy of a thermosensitive embolic agent for the treatment of pediatric renal vascular hypertension due to renal artery branch stenosis in children - Wang, Yakun; Liu, Xingmiao; Cheng, Ji; Li, Dong; Liu, Yang (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the clinical efficacy of a thermosensitive embolic agent in the treatment of renal vascular hypertension caused by stenosis in the renal artery branches.MethodsWe retrospectively analyzed 18 pediatric patients who were admitted to our hospital between March 2020 and January 2024 for interventional embolization due to hypertension caused by stenosis of renal artery branches. We compared the degree of headache relief, blood pressure, cure rate, improvement rate, changes in target organ damage, and renin levels before and after the treatment.Results(1) Clinical symptoms significantly improved, with a marked relief of headache and significant reduction in NRS-11 scores (p < 0.05). (2) Blood pressure control showed obvious improvement, with both systolic and diastolic pressures significantly lower than pre-intervention levels (p < 0.05), and the use of antihypertensive medications were reduced (p < 0.05). (3) At the 3-month follow-up, the cure and improvement rates were 55.6% (10/18) and 44.4% (8/18), respectively. At 6–12 months, the cure rate increased to 77.8% (14/18), while the improvement rate showed a corresponding decrease to 22.2% (4/18). (4) Improvement in target organ damage: At the 3-month post-intervention follow-up, echocardiographic findings of all children had returned to normal, with no signs of left ventricular hypertrophy. Both serum creatinine(Scr) and blood urea nitrogen(BUN) levels also returned to normal. Additionally, the 24 h urinary protein quantification at 3 months post-intervention was significantly lower than pre-intervention levels. During the 6–12 month follow-up period, except for one child with a mild abnormality, urinary protein indicators of all other children remained at normal levels. (5) Changes in renin levels: during the intervention, the affected renal vein demonstrated significantly elevated renin levels compared to both the contralateral renal vein and inferior vena cava (p < 0.05), while post-intervention peripheral venous renin levels were significantly lower than pre-intervention values (p < 0.05).ConclusionInterventional therapy using thermosensitive embolic agents for pediatric renovascular hypertension caused by renal artery branch stenosis demonstrated significant clinical efficacy. It effectively improved the clinical symptoms, blood pressure control, target organ damage, and renin levels of the children, with no serious complications observed during follow-up. This provides a new option for clinical treatment.Level of Evidence: Level 4, an uncontrolled clinical intervention study.